Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure! Let's solve the equation step by step:
The given equation is:
[tex]\[ 2(2x - 5) = 3x + x - 2x \][/tex]
1. First, simplify both sides of the equation.
Expanding the left side:
[tex]\[ 2(2x - 5) = 2 \cdot 2x - 2 \cdot 5 = 4x - 10 \][/tex]
Simplifying the right side:
[tex]\[ 3x + x - 2x = (3 + 1 - 2)x = 2x \][/tex]
So the equation now looks like:
[tex]\[ 4x - 10 = 2x \][/tex]
2. Next, let's get all terms containing [tex]\( x \)[/tex] on one side of the equation and the constants on the other side. Subtract [tex]\( 2x \)[/tex] from both sides:
[tex]\[ 4x - 10 - 2x = 2x - 2x \][/tex]
[tex]\[ 2x - 10 = 0 \][/tex]
3. Now, isolate [tex]\( x \)[/tex] by adding 10 to both sides:
[tex]\[ 2x - 10 + 10 = 0 + 10 \][/tex]
[tex]\[ 2x = 10 \][/tex]
4. Lastly, solve for [tex]\( x \)[/tex] by dividing both sides by 2:
[tex]\[ \frac{2x}{2} = \frac{10}{2} \][/tex]
[tex]\[ x = 5 \][/tex]
So, the solution to the equation [tex]\( 2(2x - 5) = 3x + x - 2x \)[/tex] is:
[tex]\[ x = 5 \][/tex]
The given equation is:
[tex]\[ 2(2x - 5) = 3x + x - 2x \][/tex]
1. First, simplify both sides of the equation.
Expanding the left side:
[tex]\[ 2(2x - 5) = 2 \cdot 2x - 2 \cdot 5 = 4x - 10 \][/tex]
Simplifying the right side:
[tex]\[ 3x + x - 2x = (3 + 1 - 2)x = 2x \][/tex]
So the equation now looks like:
[tex]\[ 4x - 10 = 2x \][/tex]
2. Next, let's get all terms containing [tex]\( x \)[/tex] on one side of the equation and the constants on the other side. Subtract [tex]\( 2x \)[/tex] from both sides:
[tex]\[ 4x - 10 - 2x = 2x - 2x \][/tex]
[tex]\[ 2x - 10 = 0 \][/tex]
3. Now, isolate [tex]\( x \)[/tex] by adding 10 to both sides:
[tex]\[ 2x - 10 + 10 = 0 + 10 \][/tex]
[tex]\[ 2x = 10 \][/tex]
4. Lastly, solve for [tex]\( x \)[/tex] by dividing both sides by 2:
[tex]\[ \frac{2x}{2} = \frac{10}{2} \][/tex]
[tex]\[ x = 5 \][/tex]
So, the solution to the equation [tex]\( 2(2x - 5) = 3x + x - 2x \)[/tex] is:
[tex]\[ x = 5 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.